Tāhlil āl-Insyā’ āl-Thālābi wāl Mā’ānihi fii Surāh Ghāfir - Akhmad Rusydi; Lailatul Qomariyah; Taufiqurrahman; Nida Munirah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
In studying the Arabic language, there is balaghah and there is ma'ani. Insya' thalabi of ma'ani is a sentence that requires a request before not asking. The aim is to describe the types of insya' thalabi in Surah Ghafir and their meanings. This research uses a qualitative approach with Library Research, the object of research is 58 Ayat surah Ghafir of Qur’an. The Research results: (1) found 55 words indicating insya' thalabi in 38 verses with 4 types: (a) al-amr (command) in 25 words with 24 words fi'il amar and 1-word fi'il mudhari' connected with lam al-amr; (b) an-nahi (prohibition) in 1 word in the form fi'il mudhari' which connect to lam an-nahiyah; (c) al-istifham (question) on 17 words in the form of alat: al-hamzah, hal, kaifa, min, ma, aina, ayy, anna (meaning of kaifa). 2 words indicate at-tamanni (wishful thinking) with the tools